Timing It Right: Endoscopic Necrosectomy for Infected Necrotizing Pancreatitis - Yadav, Ashutosh Ishan; Rana, Surinder Singh (Journal of Digestive Endoscopy, 2024)
The endoscopic step-up drainage approach involving initial drainage followed by, if required, direct endoscopic necrosectomy (DEN) is the preferred management approach for symptomatic pancreatic necrotic collections. However, limited data suggests that immediate DEN during initial stent placement may hasten clinical recovery by quicker resolution of systemic inflammatory response. However, because of concerns about adverse effects, especially gastric perforation and bleeding, most endoscopists prefer delayed DEN. In this news and views, we discuss a recently published randomized controlled trial that compared upfront necrosectomy at the index intervention versus as a step-up for patients with infected necrotizing pancreatitis.
Keywords: pancreatitis; lumen-apposing metal stent; necrosectomy